Identities: A developmental social-psychological perspective. Issue 1 (2nd January 2023) - Crocetti, Elisabetta; Albarello, Flavia; Meeus, Wim; Rubini, Monica
ABSTRACT: In this contribution, we review research that uses a cross-fertilisation approach to integrate developmental and social-psychological perspectives on how identities are formed and changed over time and how identity processes are genuinely social, being embedded in social contexts and fed by social contents. First, we outline the three-factor identity model as a parsimonious approach to understanding the dynamics of identity development. Second, we review empirical studies with longitudinal approaches to shed light on how identity processes are embedded in key contexts such as family, friendships and society at large through behaviours such as civic engagement. Third, we discuss the interplay between personal and social identities. We conclude by highlighting how adopting a cross-fertilisation approach that combines social-psychological and developmental perspective can significantly advance the theoretical understanding of identity dynamics. Finally, we address similarities and differences between personal identity and social identity approaches, and we provide an agenda for future research.